A Study Of Multiple Regression Analysis On Die Sinking Edm Machining Of Ex-Situ Developed Al-4.5cu-Sic Composite. (2018) - Debnath, S.; Rai, R.N.; Sastry, G.R.K.
Abstract: The synergistic relationship of Electro Discharge Machining input and output parameter of an ex-situ developed Al-4.5Cu-SiC composite has been tried to study in this paper using multiple regression analysis (MRA). Three machining parameters such as discharge current, Pulse-On time and Pulse-off time and one material parameter weight percentage of SiC are considered as controllable input parameters and metal removal rate (MRR), Surface Roughness (SR) and Tool Wear rate (TWR) considered as responses. During EDM machining process sparks breaks down the die electric fluid into a plasma state which makes the process more complicated. In this paper experimental and MRA model results are compared to the performance considered, it is observed that the developed model is within the limits of the agreeable error and it comes maximum error of 2.47% for Metal Removal Rate (MRR), 0.621% for Surface Roughness (SR) and for Tool Wear Rate (TWR) it comes 0.244%. The results show that using the MRA is a fairly accurate way of predicting the attainment of minimum tool wear against maximum metal removing with good surface finish.